Palaeolithic and prehistoric dogs and Pleistocene wolves from Yakutia: Identification of isolated skulls. (February 2017) - Germonpré, Mietje; Fedorov, Sergey; Danilov, Petr; Galeta, Patrik; Jimenez, Elodie-Laure; Sablin, Mikhail; Losey, Robert J.
Abstract: Four isolated canid skulls from four sites (Badyarikha River, Tirekhtyakh River, Ulakhan Sular, Malyi Lyakhovsky Island) in the Sakha Republic of northern Siberia are here described. Three specimens date from the Pleistocene and range in age from more than 50, 000 years to about 17, 200 years old, the fourth specimen is about 950 years old. The Yakutian canid skulls are compared with Palaeolithic dogs, recent Northern dogs, Pleistocene wolves and recent Northern wolves by multivariate analyses of standardised cranial measurements in order to determine with which reference group they have the closest affinity. These analyses permitted to identify the Tirekhtyakh River specimen as a Pleistocene wolf. The Ulakhan Sular specimen resembles the Palaeolithic dogs and the Malyi Lyakhvosky specimen the recent Northern dogs. The Badyarikha River skull falls in between groups. The archaeological implications of the presence of ancient canid specimens resembling Palaeolithic and early dogs in arctic northeast Asia are discussed. Highlights: Complete canid crania are very rare in the archaeological record. Four isolated canid skulls from northeast Asia are here analyzed. The skulls range in age from more than 50, 000 years to about 950 years old. Palaeolithic dogs have been identified from southern Siberia. Here, a Palaeolithic dog has been described from arctic northeast Asia.